Design of broadband class-F power amplifier for multiband LTE handsets applications - 郑耀华 章国豪 郑瑞清 李思臻 林俊明 陈思弟 (Journal of semiconductors, 2015)
A broadband class-F power amplifier for multiband LTE handsets applications is developed across 2.3- 2.7 GHz. The power amplifier maintains constant fundamental impedance at the output matching circuit which is operating for broadband. The nearly zero of second harmonic impedance and nearly infinity of third harmonic impedance are found for highly efficient class-F PA. The harmonic control circuits are immersed into the broad- band output matching for fundamental frequency. For demonstration, the PA is implemented in InGaP/GaAs HBT process, and tested across the frequency range of 2.3-2.7 GHz using a long-term evolution signal. The presented PA delivers good performance of high efficiency and high linearity, which shows that the broadband class-F PA supports the multiband LTE handsets applications.